Laser‐Ablated Red Phosphorus on Carbon Nanotube Film for Accelerating Polysulfide Conversion toward High‐Performance and Flexible Lithium–Sulfur Batteries. Issue 7 (19th June 2021) - Lee, Jeongyeon; Song, Hyeonjun; Min, Kyung‐Ah; Guo, Qianyi; Kim, Daekyu; Zheng, Zijian; Han, Byungchan; Jung, Youngjin; Lee, Lawrence Yoon Suk
Abstract: The use of a conducting interlayer between separator and cathode is one of the most promising methods to trap lithium polysulfides (LiPSs) for enhancing the performance of lithium–sulfur (Li–S) batteries. Red phosphorus nanoparticles (RPEN )‐coated carbon nanotube (CNT) film (RPEN @CF) is reported herein as a novel interlayer for Li–S batteries, which shows strong chemisorption of LiPSs, good flexibility, and excellent electric conductivity. A pulsed laser ablation method is engaged for the ultrafast production of RPEN of uniform morphology, which are deposited on the CNT film by a direct spinning method. The RPEN @CF interlayer provides pathways for effective Li + and electron transfer and strong chemical interaction with LiPSs. The S/RPEN @CF electrode shows a superior specific capacity of 782.3 mAh g −1 (3 C‐rate) and good cycling performances (769.5 mAh g −1 after 500 cycles at 1 C‐rate). Density functional theory calculations reveal that the morphology and dispersibility of RPEN are crucial in enhancing Li + and electron transfer kinetics and effective trap of LiPSs. This work demonstrates the possibility of using the RPEN @CF interlayer for the enhanced electrochemical performances of Li–S batteries and other flexible energy storage devices. Abstract : Pulsed laser‐ablated red phosphorus nanocrystal‐loaded carbon nanotube film (RPEN @CF) is developed as a superior conducting interlayer that provides high electric conductivity and strong chemical adsorption of lithium polysulfides (LiPSs) as well as a good flexibility for Li–S batteries. Density functional theory calculations endorse the excellent electrochemical results, demonstrating the strong Lewis acid–base interaction between RPEN @CF and LiPSs.